Faith-Based Social Entrepreneurial Orientation: Abraham is an Entrepreneur Model in Society through Faith and Business - Tjerlang Munir; Timotius Bakti Sarono; John Katrin Klamber Hutabarat; Sutrisno Sutrisno (Sekolah Tinggi Teologi Moriah, 2023)
This research investigates the relationship between religion, entrepreneurship, and social impact, using Abraham's life as an example of how these aspects can collaborate to bring about positive change in the world. Abraham's example shows how faith and business can coexist and impact the lives of his employees. As a result, Abraham is not only a role model for entrepreneurs but also an inspiration for individuals who want to make a meaningful impact on society through faith and business. This study emphasizes Abraham's example of faith and persistent entrepreneurial spirit. The aim of this research is to provide inspiration and direction for individuals who wish to combine their religion and work to make the world a better place. This paper uses a qualitative library research method, meaning that the source of this writing uses literary sources both from books and online journals related to the figure of the entrepreneur Abraham. Thus, the author builds theory and constructs Abraham's entrepreneurship and the relationship between faith and business.